Performance of dimming control scheme in visible light communication system - Wang, Zixiong (2013)
We investigate the performance of visible light communication (VLC) system with a pulse width modulation (PWM) dimming control scheme. Under this scheme, the communication quality in terms of number of transmitted bits and bit error rate (BER) of less than 10−3 should be guaranteed. However, for on-off-keying (OOK) signal, the required data rate becomes 10 times as high as the original data rate when the duty cycle of dimming control signal is 0.1. To make the dimming control scheme easy to be implemented in VLC system, we propose the variable M-QAM OFDM VLC system, where M is adjusted according to the brightness of LED light in terms of duty cycle. The results show that with different duty cycles the required data rates are not higher than the original value and less LED lamp power is required to guarantee the communication quality, which makes the dimming control system that satisfies both communication and illumination requirements easy to be implemented and power-saving.